RADIKALISME DALAM RUQYAH SHAR’IYYAH (Analisis Semiotika atas Metode Ruqyah Quranic Healing Indonesia di Youtube) - Ahmad Natsir (IAIN Ponorogo, 2018)
Abstract: The emergence of 'ruqyah aswaja' from Nahdliyin was originated from the anxiety of the present of ruqyah sunnah which tends to spread radicalism ideology. It is illustrated in the official website of Nahdatul Ulama on April 30, 2017. Ruqyah is essentially an alternative method in healing various illnesses, however, some groups of Muslims tried to utilize ruqyah for spreading radical ideology. This paper is attempted to reveal the radicalism in the ruqyah organized by QHI by the semiotic approach. It employed Roland Barthes semiotics theory to analyze the data. It focused on the value of radicalism in the ruqyah training video on Youtube uploaded by Nuruddin Al Indunissy's account which affiliated with QHI. There are two issues being discussed in this paper, The first issue is how the markers on “Hati qurani” therapy videos (ruqyah live streaming). Secondly, it deals with how to understand radicalism embedded in “Hati Qurani” therapy videos (ruqyah live training). The findings showed that the markers are in the form of giving an explanation and practice of burning keris (Javanese traditional weapon), a sign in this case of burning the cultural heritage and insulting it is a form of radicalism. The idea of radicalism lies in the intolerance of audio and visual attitudes on Javanese culture. The prevention of the spread of radicalism ideas as a 'root' of violence and it can be anticipated from the beginning would be the main implications of this paper.ملخص:الرقية هي طريقة بديلة في العلاج على مختلف الأمراض. بيد أنها مجموعات من المسلمين الذين يحاولون استخدام الرقية لنشر الأيديولوجيات المتطرفة. تحاول هذه الورقة للكشف عن التطرفات فيما وراء الرقية التي نظمتها (Quranic Healing Indonesia) QHI علي نظر السيميائي. النظرية المستخدمة هي تحليل السيميائية رولاند بارتيث. التركيز الذي سيتم تحليله هو قيمة التطرفات في فيديو “Pelatihan Ruqyah Live” المشاركة موقع التواصل الاجتماعي يوتيوب التي تم تحميلها من قبل نور الدين الإندونسي التابع لـQHIفيقتضي البحث علي القضيتين الآتيتين: أولا، ما هي الدال والمدلول في فيديو